2022
DOI: 10.3389/fendo.2022.947443
|View full text |Cite
|
Sign up to set email alerts
|

What’s the difference between lung adenocarcinoma and lung squamous cell carcinoma? Evidence from a retrospective analysis in a cohort of Chinese patients

Abstract: BackgroundLung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC) are the two most common subtypes of lung cancer. Previously, they were categorized into one histological subtype known as non-small cell lung cancer (NSCLC) and often treated similarly. However, increasing evidence suggested that LUAD and LUSC should be classified and treated as different cancers. But yet, detailed differences in clinical features between LUAD and LUSC have not been well described.MethodsA cohort of 142 Chinese patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
1
20
1
Order By: Relevance
“…NSCLC, which includes squamous and nonsquamous cell carcinomas, is the most prevalent type of lung cancer, and each of these types of NSCLC has distinct biological characteristics ( 4 ). Squamous NSCLC is generally more aggressive than nonsquamous NSCLC ( 26 ). The difference in the immune microenvironment between squamous and nonsquamous NSCLC may impact immunotherapy outcomes in patients treated with PD-1/PD-L1 inhibitors ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…NSCLC, which includes squamous and nonsquamous cell carcinomas, is the most prevalent type of lung cancer, and each of these types of NSCLC has distinct biological characteristics ( 4 ). Squamous NSCLC is generally more aggressive than nonsquamous NSCLC ( 26 ). The difference in the immune microenvironment between squamous and nonsquamous NSCLC may impact immunotherapy outcomes in patients treated with PD-1/PD-L1 inhibitors ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al. conducted a retrospective study on Chinese patients and found that platelet levels and systemic inflammation indices were significantly higher in LUSC patients than in LUAD patients, which may contribute to the tumor’s development ( 44 ). Additionally, differences in gene expression between LUSC and LUAD involve several ontological subgroups, including cell proliferation, DNA replication, and cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…With an estimated 2.2 million new cases and 1.8 million deaths in 2020, lung cancer is currently the leading cause of cancer deaths globally ( 2 ). Non-small-cell lung cancer (NSCLC) accounts for approximately 85% of all cases ( 3 ). Among the different types of NSCLC, lung adenocarcinoma (LUAD) and squamous cell carcinoma (LUSC) are the two major histological subtypes ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Non-small-cell lung cancer (NSCLC) accounts for approximately 85% of all cases ( 3 ). Among the different types of NSCLC, lung adenocarcinoma (LUAD) and squamous cell carcinoma (LUSC) are the two major histological subtypes ( 3 ). LUAD is more prevalent among non-smokers, while LUSC is strongly associated with a history of smoking, particularly among current or former heavy smokers.…”
Section: Introductionmentioning
confidence: 99%